Disentangling Specific Subsets of Innovations : A Micro-Econometric Analysis of their Determinants - Andreas Ziegler (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
Based on a unique firm-level data set from the German manufacturing sector, this paper disentangles environmental and non-environmental product and process innovations. The multivariate probit analysis shows that the various innovation types are determined by different factors. The estimation results suggest a policy mix which comprises the encouragement of R&D activities, certified management systems, and specific management activities referring to environmentally friendly products when the implementation of all innovation types is to be supported.
Keywords: Q55; O31; O32; C35; 330; Product and process innovations; Environmental and non-environmental innovations; Management systems; Multivariate probit models; Innovation; Prozessmanagement; Strategisches Management; Probit-Modell; Schätzung; Industrie; Deutschland